Spatial connectivity of Indonesian shop houses / Lya Dewi Anggraini - Anggraini, Lya Dewi (Faculty of Architecture, Planning and Surveying, 2012)
Given the very high variety of self-built shop houses in Indonesia, this paper unfolds the pattern of the shop house layout through its spatial connectivity. The method of Hillier and Hanson (1984) is modifed and used to discover the type of connectivity and its effect to the functional spaces. By analyzing samples from Chinese & Javanese settlement in Yogyakarta, the result shows that the spatial connectivity of the Chinese shop houses has the inclination of direct connectivity than is the Javanese. This may assume that in Chinese shop houses the access to the rooms is more strictly controlled and circulation is more regulated than in Javanese shop houses. Further results also show the distinct characteristic differences that are inward/outward orientation, multi-unit/single-unit, linear/cluster organization, and closeness/openness.